2021
DOI: 10.1108/cr-10-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of cloud computing in the relationship between talent management and competitive advantages

Abstract: Purpose This study aims to identify the relationship between talent management and competitive advantages through cloud computing as a mediating factor in the private health sector in Jordan. Design/methodology/approach To achieve the study, a questionnaire was developed as the main tool for data collection, which consisted of (39) paragraphs. Sequentially, the population of the study consisted of (200) outpatient clinics for private hospitals, therapeutic and diagnostic centers in the private health sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similarly, targets and deadlines are communicated to employees in their departments clearly and concisely to decrease employee turnover. Furthermore, our findings evidenced (H9) that talent retention has a significant effect on the dependent variable; most empirical research supports this positive and significant association [30,39,99,104]. Employee turnover is caused by an inability to retain valuable employees (talented) [105], directly affecting organisational costs, productivity and business performance.…”
Section: Practical Implicationsmentioning
confidence: 55%
“…Similarly, targets and deadlines are communicated to employees in their departments clearly and concisely to decrease employee turnover. Furthermore, our findings evidenced (H9) that talent retention has a significant effect on the dependent variable; most empirical research supports this positive and significant association [30,39,99,104]. Employee turnover is caused by an inability to retain valuable employees (talented) [105], directly affecting organisational costs, productivity and business performance.…”
Section: Practical Implicationsmentioning
confidence: 55%
“…The empirical findings of Dzimbiri and Molefakgotla (2021) establish that no robust application of talent management practices exists in nursing in Malawi. However, talent management’s effects on competitive advantages provided by cloud computing in the private health sector are statistically significant (Abu-Darwish et al. , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, it illustrates how underscoring the nuances of creativity's complexities can provide SMEs with the requisite resources to continue their performance. Abu-Darwish et al (2021) identified the relationship between talent management and competitive advantages through cloud computing as a mediating factor in the private health sector in Jordan. The results showed there is a statistically significant impact of talent management on the competitive advantages through cloud computing in the private health sector in Jordan.…”
Section: Related Literature In Previous Researchmentioning
confidence: 99%